Developing Noun Words Domino Card (NWDC) Learning Media to Improve English Vocabulary Mastery of Junior High School Students - Arif Bulan; Idhar Idhar (VELES Voices of English Language Education Society, 2021)
Research on the development of learning media urgently needs to be done for junior high school students. The existence of learning media is expected to increase students' understanding and mastery of certain materials. This research aims to: (1) produce a product in the form of learning media Noun Words Domino Card (NWDC) that is feasible for seventh graders of eight State Junior High School Satap Woja, (2) know the practicality of NWDC learning media for students, (3) know the effectiveness of NWDC learning media in increasing student vocabulary mastery. This research is Research and Development (R&D) by using the ADDIE model consisting of five steps: analyze design, develop, implement, and evaluate. The results showed: (1) the learning media noun words domino card (NWDC) is feasible for using and testing to students. The feasibility is based on the assessment by material experts with a feasibility value of 3.7 and media experts 3.5, (2) the learning media of noun words domino card (NWDC) is practically used in improving the vocabulary mastery of students. The practicality is based on the student's response as a user of learning media with a total average score of 3.6, (3) learning media noun words domino card (NWDC) is effective in increasing the mastery of student vocabulary. It was obtained from the average oral test score of students who passed the minimum completion criteria of English subjects.